No filter : the good, the bad, and the beautiful - Porizkova, Paulina (The Open Field/Penguin Life, 2022)
"Writer and former model Paulina Porizkova pens a series of intimate, introspective, and enlightening essays about the complexities of womanhood at every age, pulling back the glossy magazine cover and writing from the heart"--